Quantitation of triacylglycerols in plant oils using HPLC with APCI-MS, evaporative light-scattering, and UV detection - Holcapek, Michal; Lísa, Miroslav; Jandera, Pavel; Kabátová, Nadĕzda (Journal of separation science, 2005)
The main constituents of plant oils are complex mixtures of TGs differing in acyl chain lengths, number and positions of double bonds, and regioisomerism. A non-aqueous reversed-phase HPLC method with acetonitrile-2-propanol gradient and 30 + 15 cm NovaPak C18 columns makes possible an unambiguous identification of the highest number of TGs ever reported for these oils, based on positive-ion APCI mass spectra. A new approach to TG quantitation is based on the use of response factors with three typical detection techniques for that purpose (APCI-MS, evaporative light-scattering detection, and UV at 205 nm). Response factors of 23 single-acid TGs (saturated TGs from C7 to C22, 7 unsaturated TGs), 4 mixed-acid TGs, diolein and monoolein are calculated from their calibration curves and related to OOO. Due to differences between saturated and unsaturated acyl chains, the use of response factors significantly improves the quantitation of TGs. 133 TGs containing 22 fatty acids with 8-25 carbon atoms and 0-3 double bonds are identified and quantified in 9 plant oils (walnut, hazelnut, cashew nut, almond, poppy seed, yellow melon, mango, fig, date) using HPLC/APCI-MS with a response factor approach. Average parameters and relative fatty acid concentrations are calculated with both HPLC/APCI-MS and GC/ FID.
Keywords: oleje rostlin; hmotnostní spektrometrie; triglyceridy; Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Light; mastné kyseliny; Triglycerides; radiační rozptyl; Chromatography, Gas; Chromatography, High Pressure Liquid; světlo; Plant Oils; spektrofotometrie ultrafialová; Fatty Acids; Spectrophotometry, Ultraviolet; chromatografie plynová; Scattering, Radiation